The Tissue Response and Degradation of Electrospun Poly(ε-caprolactone)/Poly(trimethylene-carbonate) Scaffold in Subcutaneous Space of Mice. (3rd September 2014) - Jiang, Tao; Zhang, Guoquan; He, Wentong; Li, Hui; Jin, Xun
Abstract : Due to the advantage of controllability on the mechanical property and the degradation rates, electrospun PCL/PTMC nanofibrous scaffold could be appropriate for vascular tissue engineering. However, the tissue response and degradation of electrospun PCL/PTMC scaffold in vivo have never been evaluated in detail. So, electrospun PCL/PTMC scaffolds with different blend ratios were prepared in this study. Mice subcutaneous implantation showed that the continuous degradation of PCL/PTMC scaffolds induced a lasted macrophage-mediated foreign body reaction, which could be in favor of the tissue regeneration in graft.